Предмет: Алгебра,
автор: likanerasova
Срочно!!!Пожалуйста!!!Срочно
Приложения:
Ответы
Автор ответа:
0
а) 2^2- (-3)^2 = 4 -9=-5
б) (-2 1/2)^3 * 0.064= -( 5/2)^3 *( 2/5)^3= -( 5/2 * 2/5 )^3 = -1
в) (-5)^4 * (-2/5)^4 = (5 * 2 / 5)^4= 2^4= 16
номер 2
а) (х^4)^3 / х^11 * х = х^12 / х ^12 = 1
б) (-0.2 аb^5)^3= - 0.008a^3*b^15
в) (6х)^2* (х*х^5)^4 = 36х^2 * х^24 = 36 х^26
б) (-2 1/2)^3 * 0.064= -( 5/2)^3 *( 2/5)^3= -( 5/2 * 2/5 )^3 = -1
в) (-5)^4 * (-2/5)^4 = (5 * 2 / 5)^4= 2^4= 16
номер 2
а) (х^4)^3 / х^11 * х = х^12 / х ^12 = 1
б) (-0.2 аb^5)^3= - 0.008a^3*b^15
в) (6х)^2* (х*х^5)^4 = 36х^2 * х^24 = 36 х^26
Похожие вопросы
Предмет: Математика,
автор: allnxz
Предмет: Английский язык,
автор: aabud428
Предмет: Қазақ тiлi,
автор: amir2003m
Предмет: Математика,
автор: olhanushcha